Ideal Cardiovascular Health Metrics Attenuated Association of Age at Menarche With Type 2 Diabetes in Rural China - Xueyan Wu; Lei Bao; Xiaotian Liu; Wei Liao; Ning Kang; Shengxiang Sang; Tanko Abdulai; Zhihan Zhai; Chongjian Wang; Yuqian Li (Frontiers Media S.A., 2022)
Objective: It is not clear whether ideal cardiovascular health (ICH) metrics have an impact on the association between age at menarche and type 2 diabetes (T2DM) in rural postmenopausal Chinese women.Methods: In all, 15,450 postmenopausal women were enrolled from the Henan Rural Cohort study. Logistic regression models and interaction plots were used to analyze associations between age at menarche, ICH metrics and T2DM and interactive effects.Results: Age at menarche was inversely associated with risk of T2DM, with adjusted OR of 1.224, 1.116, 1.00 and 0.971, 0.850 for those with age at menarche ≤13, 14, 15-16 (reference), 17, and ≥18 years, respectively, and each year of delay in menarche age correlated with a 5.1% lower risk of T2DM. Negative interaction effects of age at menarche and number of ICH metrics on the risk of T2DM was observed.Conclusion: Meeting more ICH metrics might attenuate the association between early menstrual age and increased risk of T2DM, implying that meeting a higher number of ICH metrics may be an effective way to prevent T2DM for women of early menarche age.